Karakterisasi POC (Pupuk Organik Cair) Berbasis Limbah Dapur Dari Universitas Darussalam Gontor Kampus Putri (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2022)
Kitchen waste, either the organic or the inorganic ones, accumulated on landfills causes environmental and health problems. Composting is an alternative that reduces environmental problems while producing Liquid Organic Fertilizers (LOF). This research was aimed to examine the LOF character made of organic kitchen waste from Darussalam Gontor University, Girls Campus. The research was conducted by composting 10 kg of kitchen waste (comprised of banana peel, rotten watermelon, and vegetable waste), 20 liters of rice washing water, 10 kg of eggshell, 1 kg of sugar, 1 liter of EM4 (decomposing microorganism), and 80 liters of water. The liquid fertilizer produced was analyzed physically, namely from the color, smell, and presence of insect larvae. Chemical analysis was carried out for the content of C-organic, organic matter N, P, and K). C-organic and other organic matter content were analyzed using the Walkley & Black method. Total N content was analyzed using the Kjeldahl method. The content of P and K were analyzed by the extraction method of HNO3 and HClO4. The liquid fertilizer produced was yellowish-brown in color, did not have a bad smell, and did not contain insect larvae. Its nutrient content, respectively C-organic, other organic matters, N, P, and K were 0.74%; 1.27%; 0.13%; 0.015%; and 0.10%. The fertilizer produced had not met the standards of the Ministry of Agriculture No. 261 of 2019. Further studies are needed with the addition of animal manure and the composition of the ratio of organic matter to water. Limbah organik dapur yang dibuang di tempat pembuangan akhir (TPA) menimbulkan permasalahan lingkungan dan kesehatan. Pengomposan sebagai salah satu alternatif mengurangi masalah lingkungan dari limbah organik dapur dan menghasilkan POC (Pupuk Organik Cair). Penelitian ini bertujuan untuk mengkaji karakter POC limbah organik dapur dari Universitas Darussalam Gontor Kampus Putri. Penelitian dilakukan dengan cara mengomposkan limbah dapur 10 kg (kulit pisang, semangka busuk dan limbah sayuran), air cucian beras 20 L, cangkang telur 10 kg, gula 1 kg, EM4 1 L dan air 80 L. POC yang dihasilkan dianalisa secara fisik (warna, bau dan kehadiran larva serangga) dan analisa kimia (kandungan C-organik, bahan organik, N, P dan K). Kandungan C-organik dan Bahan organik dianalisa dengan metode Walkley & Black. Kandungan N total dianalisa dengan menggunakan metode Kjeldhal. Kandungan P dan K dianalasi dengan metode ekstraksi HNO3 dan HClO4. POC yang dihasilkan berwarna coklat kekuningan, tidak berbau busuk dan tidak mengandung larva serangga. Kandungan unsur hara POC yaitu: C organik 0,74%; bahan organik 1,27%; N 0,13%; P 0,015%; K 0,10%. POC yang dihasilkan belum memenuhi standar Permentan No. 261 Tahun 2019, sehingga perlu kajian lebih lanjut dengan komposisi penambahan kotoran hewan dan komposisi perbandingan bahan organik dengan air.